Nursepreneur Education on Nurse Communication in Vocational High Schools - Mirasari, Triana; Talango, Farid; Mardiah, Adriana (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
A strong nursepreneur is able to work independently, has a vision, is creative, and dares to take risks. Nurse communication is the foundation for the success of a nurse's dual role. The aim of this community service is to improve the quality of knowledge services provided as an important role in the success and growth of the rescue business. The aspect measured is increased knowledge. Service is carried out by providing education to students. Before providing education, it was carried out by giving a pre-test questionnaire and interviews with the results of students' knowledge regarding nursepreneurs regarding nurse communication was lacking and after providing education a post-test was given with the results of students' knowledge increasing. 60 vocational school students from the nursing skills program participated in this educational event enthusiastically paying attention to PPTs, leaflets, lectures and discussions for 45 minutes. The results of this service show an increase in students’ knowledge by actively participating with the resource persons. The conclusion of this service is that nurse communication is the first step for novice nursepreneurs as nursepreneurs in the world of very tight economic competition. Therefore, schools should provide good student communication practice laboratories.